(untitled) (International Journal of Engineering and Computer Science, 2014)
The basic idea of the Visual Cryptography is to encrypt a secret image into n number of meaningless share images. The Visual Cryptography technique cannot leak the encrypted information of the shared secret by virtue of any combination of the n share images combined together. This share images are printed on separate transparencies and distributed as shares such that, when the share images are superimposed, the concealed secret image is discovered. Thus, the human visual system can recognize the shared secret image without using any computational devices. There is no need of cryptography knowledge and complex computation. The traditional visual secret sharing scheme uses a pre-defined pattern book to generate shares, which leads to a pixel expansion problem on share images. Basically, the performance of visual cryptography scheme depends on different measures like pixel expansion, security, contrast, computational complexity, accuracy, share generated, number of secret images and type of secret images encrypted by the scheme. Objective of this paper is on study and performance analysis of the visual cryptography schemes without pixel expansion, number of secret images, type of the image and type of shares generated (meaningless or meaningful).